2014
DOI: 10.1159/000362921
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functioning after Carotid Revascularization: A Systematic Review

Abstract: Background: The objective of this study was to review the recent literature regarding the neurocognitive consequences of carotid endarterectomy (CEA) and carotid stenting (CAS). Methods and Results: A PubMed and Web of Science search was conducted using the key words ‘carotid' in combination with ‘cognitive', ‘cognition', ‘neurocognition', ‘neurocognitive', ‘neuropsychology', and ‘neuropsychological'. Bibliographies of relevant articles were cross-referenced. We included 37 studies published since 2007 of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 67 publications
8
46
0
Order By: Relevance
“…None of the 18 variables showed a significant group difference, and only one showed a small interaction effect. The fact that CEA and CASdp have similar effects on cognition is in agreement with previous research (Paraskevas et al, 2014;Plessers et al, 2014). We now showed that also direct access using flow reversal does not lead to any significant cognitive changes compared with other techniques.…”
Section: Outcome After Carotid Revascularizationsupporting
confidence: 92%
See 4 more Smart Citations
“…None of the 18 variables showed a significant group difference, and only one showed a small interaction effect. The fact that CEA and CASdp have similar effects on cognition is in agreement with previous research (Paraskevas et al, 2014;Plessers et al, 2014). We now showed that also direct access using flow reversal does not lead to any significant cognitive changes compared with other techniques.…”
Section: Outcome After Carotid Revascularizationsupporting
confidence: 92%
“…Exclusion criteria were history of previous carotid interventions, coronary artery bypass grafting, or stroke within 2 years, age >80 years, psychiatric or neurological disorders, alcohol abuse, and a Mini Mental State Examination (MMSE) score lower than 24. Following Plessers et al (Plessers et al, 2014), to avoid any influence of recent brain damage on the possible cognitive changes evoked by revascularization, symptomatic patients were also excluded if they had had a stroke. Consequently, only symptomatic patients that had experienced a TIA and/or amaurosis fugax were included.…”
Section: Patients and Controlsmentioning
confidence: 99%
See 3 more Smart Citations